KONSEP PENDIDIKAN ISLAM DALAM TAFSIR IBNU KATSIR (Studi Atas QS. Luqman [31]: 12–19) - Ahmad Saoki Munjaji; Acep Rahmat; Ahmad Jamal Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the concept of Islamic education contained in QS. Luqman [31]: 12–19 using a thematic interpretation approach (maudhu’i) and content analysis techniques based on Ibn Kathir’s interpretation. The primary data sources are verses of QS. Luqman [31]: 12–19 along with Ibn Kathir’s interpretation, while secondary data are obtained from contemporary Islamic education literature and reputable scientific journal articles. The results of the study indicate that QS. Luqman [31]: 12–19 presents an integrative and systematic concept of Islamic education, including education on faith as the basis of monotheism, worship education for spiritual strengthening, moral education and social ethics in shaping behavior, and character education that emphasizes self-control, patience, and social responsibility. These findings confirm that the model of Al-Qur’anic education through Luqman’s advice is not only normative, but also contextual and applicable in responding to the challenges of contemporary Islamic education, especially related to the moral crisis and the weak religious character of students. This research provides a conceptual contribution to the development of Islamic education based on the Qur'an and recommends the integration of the values ​​of QS. Luqman [31]:12–19 in the development of the Islamic Religious Education curriculum and educational practices in the family and school environment.